Personal Branding Content Creator Arif Muhammad (Analisis Visual pada Akun Youtube @Arif Muhammad) - Amalia, Tri Wahyu; Satvikadewi, A.A.I. Prihandari (Universitas 17 Agustus 1945 Surabaya, 2020)
The emergence of more content creator, is the impact of social media development, especially youtube. Youtube became the most accessible platform on 2019. It requires content creators to create quality content and form personal branding, so they can compete and get recognition. This research will reveal the personal branding of a youtube content creator, namely Arif Muhammad or Mak Beti, who is trending on youtube because of his comedy content as a multirole. This qualitative study examines one video on @Arif Muhammad's youtube account, titled